1980
DOI: 10.1159/000123076
|View full text |Cite
|
Sign up to set email alerts
|

ACTH Regulation of Tissue-CRF

Abstract: The influence of the anterior pituitary on tissue CRF was investigated in two sets of experiments using lesioned, hypophysectomized, adrenalectomized donor rats. Donors were injected with 1 or 0.5 anterior pituitary equivalents 3 h before transfer of plasma to recipient animals. Injection of 1 pituitary equivalent significantly reduced levels of corticosterone in recipient rats compared to saline injection at 3 different time intervals following the transfer. In a second series of experiments donor animals rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1983
1983
2006
2006

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…It is possible that the factor described in the present study is related to a peripheral corticotroph-stimulating factor pre viously reported to be released following tissue injury [6,II,18,19,31]. Lymangrover and Brodish [18,19] detected such a fac tor in the blood of rats who had undergone laparotomies with intestinal exteriorization and manipulation.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…It is possible that the factor described in the present study is related to a peripheral corticotroph-stimulating factor pre viously reported to be released following tissue injury [6,II,18,19,31]. Lymangrover and Brodish [18,19] detected such a fac tor in the blood of rats who had undergone laparotomies with intestinal exteriorization and manipulation.…”
Section: Discussionmentioning
confidence: 66%
“…Five hours after the laparotomies, the blood was injected into recipient rats, resul ting in a increase in circulating corticosterone. The increase in corticosterone required an intact pituitary in the recipient rat, implying that the factor acts at the level of the pituitary cortico troph cell [18,19,31]. In addition to surgical trauma, thermal injuiy can also evoke peripheral release of a CRF-like factor.…”
Section: Discussionmentioning
confidence: 99%